The inhibition effect of CTAB and Triton X-100 surfactants on the corrosion of nickel in alkaline solution - Mojgan Rajabi; Ali Arab; Ahmad Bagheri (شیمی کاربردی روز, 2021)
In this paper, the effect of CTAB and Triton X-100 surfactants as nickel corrosion inhibitors in alkaline solution at three temperatures of 25, 40, and 60 0C was investigated. The Tafel polarization method was used to determine the corrosion potential, corrosion current intensity, and anodic and cathodic Tafel slopes. The inhibition performance of these two surfactants was studied separately and also in the form of a mixture of these two surfactants with different ratios. The results showed that in all three temperatures, by adding the surfactant to the medium, the nickel corrosion rate was reduced. The obtained optimum concentration for CTAB and Triton X-100 was 150 ppm and 200 ppm, respectively. The results of the adsorption isotherms showed that the adsorption of CTAB and Triton X-100 followed the Langmuir model. The synergistic effect of these two surfactants was also investigated and results showed that when the mixture of the two surfactants was used the inhibition efficiency was increased significantly which indicated the better performance of the surfactants mixture for the protection of nickel.